Análisis comparativo de las configuraciones del tejido urbano y sus relaciones con la movilidad del plan parcial Triángulo Bavaria (2016)
The work presented here is the result of a project of urban design instruments that consented to develop the theme of the relationship between urban mobility, road fabric and the distribution of the blocks of the city. For this, there was a need, as a priority, to conceptualize and create research that would allow us to combine diverse contemporary visions around the issue of mobility and road tissue.